Export, Foreign Direct Investment and Gross Domestic Product: Case of the Commonwealth of Independent States Countries and Armenia - Lilit N. Sargsyan (Регионология, 2019)
Introduction. Export and foreign direct investment have great significance for economic development of the developing and transition countries, like Armenia and the Commonwealth of Independent States countries. As the domestic market of the Republic of Armenia is small, Armenia’s economic development depends on external demand. The aim of this article is to estimate the impact of foreign direct investment and export on gross domestic product of the Commonwealth of Independent States countries and the Republic of Armenia.